POLYCYSTIC OVARY SYNDROME, LACTOGENESIS AND BREASTFEEDING - Irena Hren; Darija Mateja Strah (The Society for Children with Metabolic Disorders, 2023)
Because of its known benefits for mother and baby, breastfeeding should be introduced within the first hour after birth and should be the only way to feed a newborn for the first six months. Women with polycystic ovary syndrome (PCOS) have been described as having a poorer breastfeeding success rate, which may be related to their high obesity rate. Both obesity and PCOS inhibit breastfeeding initiation and maintenance. To date, in population-based studies no independent association between PCOS and breastfeeding performance has been identified. Delayed lactogenesis is particularly common in mothers with obesity or diabetes. Reasons for stopping breastfeeding may be physiological, psychological, personal and environmental. Endocrinological reasons for the reduced breastfeeding success in PCOS patients lie in the altered hormonal status of the mother. In addition to other factors, elevated levels of androgen hormones after childbirth further impede the developing lactation and altered insulin dynamics may also contribute to a poorer breastfeeding outcome. In this paper, we discuss impaired lactogenesis in women with PCOS and possible measures to improve breastfeeding success, with emphasis on the importance of managing maternal obesity before, during and after pregnancy. The key areas for action in women with PCOS are poorer breastfeeding initiation and shorter breastfeeding duration. All mothers with PCOS should be encouraged to breastfeed and provided with effective lactation support.